Factors Related To Formula Feeding To Babies Aged 0-6 Months In Work Area Of Balai Jaya Health Center - Liva Maita; Octa Dwienda Ristica; Kiki Megasari; Zunaida Zunaida (Lembaga Publikasi Ilmiah Nusantara, 2026)
Formula feeding among infants aged 0-6 months remains a public health concern because it can reduce exclusive breastfeeding and increase infant health risks. This study aimed to identify factors associated with formula feeding among infants aged 0-6 months in the working area of Balai Jaya Health Center, Rokan Hilir Regency, in 2025. This research used a quantitative cross-sectional design. The population comprised all mothers of infants aged 0-6 months, and 74 respondents were selected through total sampling. Data were collected using questionnaires and analyzed through univariate analysis and chi-square tests at a significance level of p < 0.05. The results showed that 60.8% of infants received formula milk. Most mothers had low levels of knowledge, negative attitudes, were working, were exposed to formula milk promotion, and lacked family support. Bivariate analysis showed significant associations between knowledge, attitude, employment status, formula milk promotion, and family support and formula feeding (p-values = 0.000). This study concludes that these factors are associated with formula feeding. Therefore, continuous education, lactation counseling, workplace support, and family involvement are needed to strengthen exclusive breastfeeding practices and prevent inappropriate early formula use among infants in the local community.